Estimate of in vitro embryo production based on sperm subpopulations in Senepol bulls - Peres Campanholi, Suzane [UNESP]; Garcia Neto, Sebastião; Basso, Andréa Cristina; de Agostini Losano, João Diego; Perez Siqueira, Adriano Felipe; Nichi, Marcílio; Ortiz D'Avila Assumpção, Mayra Elena; Afonso de Freitas, Luara; Paro de Paz, Claudia Cristina; Ferraudo, Antonio Sérgio [UNESP]; Morato Monteiro, Fabio; Unno Gimenes, Lindsay [UNESP] (Elsevier, 2021)
In cattle, in vitro embryo production (IVEP) is an important reproductive biotechnology responsible for the rapid expansion of the Senepol breed in our country. This breed has shown important results when used in crossbreeding and estimate IVEP in Senepol based on seminal analysis would be valuable for the semen cryopreservation industry, research institutes and breeders. Combining the evaluation of sperm subpopulations with analysis of other sperm attributes may help to improve fertility predictions in cattle. Therefore, the objectives of the present study were to: 1) identify and characterize motile sperm subpopulations in cryopreserved Senepol semen following the washing process carried out before in vitro fertilization, and 2) to determine an model for estimate IVEP based on sperm subpopulations in conjunction with other sperm quality analyzes. Samples of 38 cryopreserved semen from 28 Senepol bulls, chosen based on retrospective data from 386 IVEP routines, underwent the semen washing and were evaluated by the computer-assisted sperm analysis system. Sperm morphology was evaluated by wet preparation technique, and plasma and acrosomal membranes integrity, mitochondrial potential, oxidative status and chromatin resistance were analyzed by flow cytometry. After multivariate analysis of principal components and grouping, three sperm subpopulations were identified: SBP1 (fast and progressive motility), SBP2 (hyperactivated motility) and SBP3 (slow non-progressive motility). After categorization of IVEP in high, medium and low embryo yield, logistic regression analysis was applied to associate the results of subpopulations and other sperm quality variables with IVEP. The SBP1 and SBP2 variables affected embryo production, and an IVEP estimation model was generated for Senepol bulls based on these two subpopulations: embryo yield = 0.1563 + 0.0328 (SBP1) + 0.0173 (SBP2). SBP1 and SBP2 represents the absolute value of the percentage of subpopulations in semen. If the calculated value (by this equation) is close to 1, the embryo yield will be low; if is close to 2, will be medium; if is close to 3, will be high. In conclusion, three subpopulations were found for Senepol semen and, despite all analyzed variables, only SBP1 and SBP2 were included in the model to estimate IVEP in this breed.
Keywords: Bovine; Fertility; Kinetic parameters; Motility; Sperm